Aortic balloon occlusion (REBOA) in pelvic ring injuries: preliminary results of the ABO Trauma Registry - Federico Coccolini (2020)
© 2020, Italian Society of Surgery (SIC). EndoVascular and Hybrid Trauma Management (EVTM) has been recently introduced in the treatment of severe pelvic ring injuries. This multimodal method of hemorrhage management counts on several strategies such as the REBOA (resuscitative endovascular balloon occlusion of the aorta). Few data exist on the use of REBOA in patients with a severely injured pelvic ring. The ABO (aortic balloon occlusion) Trauma Registry is designed to capture data for all trauma patients in hemorrhagic shock where management includes REBOA placement. Among all patients included in the ABO registry, 72 patients presented with severe pelvic injuries and were the population under exam. 66.7% were male. Mean and median ISS were respectively 43 and 41 (SD ± 13). Isolated pelvic injuries were observed in 12 patients (16.7%). Blunt trauma occurred in 68 patients (94.4%), penetrating in 2 (2.8%) and combined in 2 (2.8%). Type of injury: fall from height in 15 patients (23.1%), traffic accident in 49 patients (75.4%), and unspecified impact in 1 patient (1.5%). Femoral access was gained pre-hospital in 1 patient, in emergency room in 43, in operating room in 12 and in angio-suite in 16. REBOA was positioned in zone 1 in 59 patients (81,9%), in zone 2 in 1 (1,4%) and in zone 3 in 12 (16,7%). Aortic occlusion was partial/periodical in 35 patients (48,6%) and total occlusion in 37 patients (51,4%). REBOA associated morbidity rate: 11.1%. Overall mortality rate was 54.2% and early mortality rate (≤ 24 h) was 44.4%. In the univariate analysis, factors related to early mortality (≤ 24 h) are lower pH values (p = 0.03), higher base deficit (p = 0.021), longer INR (p = 0.012), minor increase in systolic blood pressure after the REBOA inflation (p = 0.03) and total aortic occlusion (p = 0.008). None of these values resulted significant in the multivariate analysis. In severe hemodynamically unstable pelvic trauma management, REBOA is a viable option when utilized in experienced centers as a bridge to other treatments; its use might be, however, accompanied with severe-to-lethal complications.